Goals of Community Colleges in Canada A 1987 Perspective - Dennison, John D.; Levin, John S. (Canadian Journal of Higher Education, 1988)
Community colleges in Canada are characterized by diversity with respect to their relations with the government, the scope and range of their programs, and the ways in which they respond to societal needs. Nevertheless, the colleges all share a commitment to providing access to a wide range of individuals who need educational opportunities beyond secondary school. This study examines the goals of community colleges in Canada as perceived by two key groups - chief executive officers, and government personnel in each province who are responsible for college development. The prime purpose was to determine the degree to which these individuals agree on the rating and ranking of their goals and the variations which exist among the provincial systems. The results indicate that provincial college systems have continued to emphasize the goals which characterized their early development and reflect the differences in priorities which occur by province. While the two groups showed a high level of agreement in each region, a range of priorities existed within each group. In general, the study provided a restatement of the diversity of ways in which Canada's colleges are attempting to contribute to the economic, sociocultural, and educational development of the nation.